Efesiensi Tataniaga Cabai Rawit di Kabupaten Kotawaringin Barat - Novi Nurhayati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
Marketing Chili pepper is unique marketing, where the price of chili is always fluctuating. In marketing, chili pepper involves marketing institutions that have a significant role in channeling chili pepper from producers to consumers. The purpose of this research is to know the channel, institution, a function of the marketing institution as well as the affection of the marketing Tataniaga of chili pepper in Kotawaringin Barat Regency. The study was conducted at Pangkalan Bun, from July - September 2019. The method of research used is a descriptive method to know the channel, and the function of the marketing institution, while to know the efficiency of chili pepper, the use of marketing margin analysis and farmer’s share. The result of this research is a channel of cayenne Pepper in Kotawaringin Barat district there are three levels of marketing channels, namely two-level channels, three-level channels, and four-level channels. The marketing institutions involved in cayenne pepper include collector merchants, wholesalers, and retailers. Collector traders have the function of collecting chili pepper from the farmer and resell it, wholesalers have the function of buying chili pepper from the collecting merchant and resell it, while the retail trader has the function of buying chili From collecting merchants and wholesalers and selling directly to consumers. The marketing efficiency of chili pepper in Kotawaringin Barat District is on the Marketing Channel 2 (two) levels, with a marketing margin worth Rp. 40,000., and farmers share by 72.41%.